FORMULATION AND EVALUATION OF TRAZODONE HYDROCHLORIDE ORODISPERSIBLE TABLETS - D, Akiladevi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the existing research was to develop an oral disintegrating dissolving system as one of the taste masking orodispersible forms together of trazodone hydrochloride tablets using direct compression technique through the use of superdisintegrants together with FlowLac, StarLac, and sodium starch glycolate. Methods: The tablets were formulated using the direct compression approach. The drugs prepared have been evaluated for diverse parameters which include hardness, friability, weight variation, drug content uniformity, water absorption ratio, in vitro drug release, and wetting time. Results: The hardness of all formulations from F1 to F7 proved that the tablet means thickness was nearly uniform in all formulations with the range of 0.520 mm–0.522 mm. Water absorption of prepared formulations was found to be 68.59%–73.21%. Bulk density, tapped density, and friability of the formulations were established within the limits, results of in vitro drug release study showed the drug released between 90.27% and 96.17% at 60 min. Conclusion: The overall study concluded that orodispersible tablets of trazodone hydrochloride have greater dissolution rate and will result in enhanced bioavailability. The taste masked systems are designed to provide better acceptability, improved bioavailability, for chronic patients. The study results revealed that the formulation F6 was contemplated as the top formulation.